Review on Preservation of Post-Harvest Vegetables by Using Evaporative Cooling Method - Husainy, Avesahemad S. N.; Sawant, Prasad Maruti; Yusuf Shaikh, Sayeedahmed M.; Virbhadre, Om Shashikant; Tone, Mayuresh Sanjay (Asian Journal of Engineering and Applied Technology, 2021)
Proper storage of vegetables, fruits and food items is necessary in order to maintain their life. The shelf life of vegetables is highly dependent on temperature and humidity in storage place. Cold room and refrigeration facilities are out of budget due to advance technologies and high electricity consumption. Affordable storage facility is highly useful in such conditions. The paper aims at developing low cost, small scale evaporative cooler that operates on a principle of evaporative cooling phenomenon. The developed model has box type of structure having water holding vessel at bottom side. The proposed model has cooling fan arranged for vertical orientation with certain height partial closed as well as medium height between cooling chamber and storage chamber. The fan has been operated at two speed variants namely low speed as well as high speed for getting results at different evaporation rates. Throttling vanes have been provided through the air entering chamber which significantly affects evaporation capacity of the evaporative box. In the given range of 270 minutes of operating time during two time slots i.e.,morning and afternoon. Humiditypercentage increase from 26 to 60 is found through the experimentation while the temperature difference was reduced down to 8 degrees of difference (40 ⁰C to 32 ⁰C) through experimentation. The performance of the developed model was found better in case of throttling with fan speed parameter that includes partial throttling at high speed and medium throttling at low speed.